Toward a comprehensive care of HIV patients: finding a strategy to detect depression in a Spanish HIV cohort. Issue 7 (2nd July 2016) - Bayón-Pérez, C.; Hernando, A.; Álvarez-Comino, M.J.; Cebolla, S.; Serrano, L.; Gutiérrez, F.; Montesinos, F.; Lagarde, M.; Bisbal, O.; Matarranz, M.; Rubio, R.; Pulido, F.
ABSTRACT: Depression is a common but frequently undiagnosed feature in individuals with HIV infection. To find a strategy to detect depression in a non-specialized clinical setting, the overall performance of the Hospital Anxiety and Depression Scale (HADS) and the depression identification questions proposed by the European AIDS Clinical Society (EACS) guidelines were assessed in a descriptive cross-sectional study of 113 patients with HIV infection. The clinician asked the two screening questions that were proposed under the EACS guidelines and requested patients to complete the HADS. A psychiatrist or psychologist administered semi-structured clinical interviews to yield psychiatric diagnoses of depression (gold standard). A receiver operating characteristic (ROC) analysis for the HADS-Depression (HADS-D) subscale indicated that the best sensitivity and specificity were obtained between the cut-off points of 5 and 8, and the ROC curve for the HADS-Total (HADS-T) indicated that the best cut-off points were between 12 and 14. There were no statistically significant differences in the correlations of the EACS (considering positive responses to one [A] or both questions [B]), the HADS-D ≥ 8 or the HADS-T ≥ 12 with the gold standard. The study concludes that both approaches (the two EACS questions and the HADS-D subscale) are appropriate depression-screening methods in HIV population. We believe that using the EACS-B and the HADS-D subscale in a two-step approach allows for rapid, assumable and accurate clinical diagnosis in non-psychiatric hospital settings.